POLYPLOIDY INDUCED BY COLCHICINE IN Robinia pseudoacacia L. AND IT'S EFFECTS ON MORPHOLOGICAL, PHYSIOLOGICAL AND ANATOMICAL SEEDLING TRAITS - & Asander, Suliman (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to induce and produce a polyploidy Robinia pseudoacacia seedling by different concentrations of colchicine (0.0%, 0.5%, 1.0%, 1.5%, and 2.0%) in various exposure times (12, 24 and 48 h), using in two experiments. In the first, were applied to the seeds by immersing method. In the second, were applied to shoot apical meristems by dropping method. The results showed significant effects of different interactions between colchicine concentration and exposure period on the seed germination, seedling survival rate and seedling characters. By increasing of the colchicine concentration the seed germination and seedling survival rate decreased significantly in colchicine concentrations (0.15 and 0.2%). Frequency of stomata decreased and on the opposite the stomata length and width increased with increases the colchicine concentrations. Polyploidy seedlings show vegetative growth superiority yield compared to diploids seedlings, leaf area in treated plants was larger and with deep green pigmentation as compared to the control seedlings. Seed treatment method was found to be more efficient than shoot apical meristems treatment method in producing tetraploid and mixoploid plants, colchicine solutions at 0.1% and 1.5% in 24 h. and 48 h. was found most effectively produced polyploidy and inducing variation in both investigations.